Face sheep recognition using artificial intelligence - Atallah Abdelali; Kamal Sehairi (University Of Amar Telidji Laghouat- Faculty Of Technology- Electronics Department, 2025)
This thesis focuses on designing and developing an intelligent system for sheep identification using artificial intelligence and computer vision techniques. The system follows multiple stages, starting with data collection, face detection from images, feature extraction for each sheep, and finally classification using machine learning algorithms. The main goal of this work is to help farmers by providing an automatic and accurate tool for sheep identification without the need for manual checking each time. The system was applied and tested on real sheep images collected in a local environment. The results showed promising performance despite some challenges.
Networks and telecommunications